Pendekatan Apresiasi dan Ekspresi Berbantuan Media Audiovisual Pada Pembelajaran Musik Mancanegera Di SMAN 13 Padang - Faiz Oktavian; Tulus Handra Kadir (Politeknik Kampar, 2023)
This research aims to describe the implementation of foreign music learning in class XII science 2 at SMAN 13 Padang. This type of research is qualitative with descriptive methods. The instrument in this research was the researcher himself and was assisted with supporting instruments in the form of writing equipment and a camera. Data collection techniques include observation, interviews, documentation and literature study. The data in this research uses primary and secondary data. The steps to analyze data are collecting data, identifying data, classifying data, describing and concluding data. The research results show that the learning process is going well and the teacher uses the RPP as a reference in learning even though the teacher has not carried out all the activities in the RPP. Students are helped by the audiovisual media provided by the teacher. This is proven by the percentage of 100% of students getting a score above the KKM with the lowest score being 84.